Revision of the Hylaea fasciaria (Linnaeus, 1758) species group in the western Palaearctic (Lepidoptera: Geometridae, Ennominae) - Sihvonen, Pasi; Skou, Peder; Flamigni, Claudio; Fiumi, Gabriele; Hausmann, Axel (Zootaxa, 2014)
The Palaearctic Hylaea fasciaria (Linnaeus, 1758) species group is revised (Lepidoptera: Geometridae, Ennominae). Four taxa are considered valid at species level: H. fasciaria (Linnaeus, 1758), H. pinicolaria (Bellier, 1861), H. compararia (Staudinger, 1894) and one new species, H. mediterranea, from Italy: Sicily, Calabria and Molise. The following taxonomic changes are proposed: Ellopia cedricola Wehrli, 1919, from Turkey is downgraded to subspecies of Hylaea fasciaria (Linnaeus, 1758) (revised status), Hylaea fasciaria cleui Leraut, 1993, from France is downgraded from subspecies to synonymy with H. fasciaria fasciaria (Linnaeus, 1758) (new synonymy) and Ellopia compararia Staudinger, 1894, from Algeria is raised from subspecies of Hylaea fasciaria (Linnaeus, 1758) to species status (revised status). Hemithea squalidaria O. G. Costa, 1848 from southern Italy was placed in the genus Hylaea, but it is reverted to its original combination as its taxonomic status is uncertain. Adults, male and female genitalia and distribution maps are illustrated for all species. DNA barcodes are presented for most taxa studied.